2012
DOI: 10.1007/s00702-012-0902-z
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation combined with cognitive training is a safe and effective modality for the treatment of Alzheimer’s disease: a randomized, double-blind study

Abstract: Cortical excitability can be modulated using repetitive transcranial magnetic stimulation (rTMS). Previously, we showed that rTMS combined with cognitive training (rTMS-COG) has positive results in Alzheimer's disease (AD). The goal of this randomized double-blind, controlled study was to examine the safety and efficacy of rTMS-COG in AD. Fifteen AD patients received 1-h daily rTMS-COG or sham treatment (seven treated, eight placebo), five sessions/week for 6 weeks, followed by biweekly sessions for 3 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(229 citation statements)
references
References 28 publications
6
222
0
1
Order By: Relevance
“…Most studies included elderly with mild cognitive impairments [35, 36, 41-43, 47, 49-51, 53, 55, 56], some studies included elderly at risk for dementia [38,52,58], some other studies patients with mild to moderate dementia [37,46,57], moderate to severe dementia [34,48], diagnosed with Alzheimer disease [39,40,44,45,48,51,54].…”
Section: Skills Training Trialsmentioning
confidence: 99%
“…Most studies included elderly with mild cognitive impairments [35, 36, 41-43, 47, 49-51, 53, 55, 56], some studies included elderly at risk for dementia [38,52,58], some other studies patients with mild to moderate dementia [37,46,57], moderate to severe dementia [34,48], diagnosed with Alzheimer disease [39,40,44,45,48,51,54].…”
Section: Skills Training Trialsmentioning
confidence: 99%
“…Moreover, the majority of the studies have focused on memory, the core clinical symptom. Ten studies were designed as multiple session paradigm [81, 83, 84, 86-88, 90, 92-94], and a cognitive training was combined with the stimulation protocol in 3 of the brain stimulation studies on AD [84, 93, 94]. …”
Section: Nibs and Dementiamentioning
confidence: 99%
“…High frequency (HF) rTMS applied on the right or left DLPFC has shown improvement in language abilities, in cognitive function, functionality and behavior for up to 3 months (5). Other studies have shown similar results on cognition, behavior and function using HF applied over several cortical sites in a complex design (6). This complex design may include at least 6 cortical targets, and it is suggested to be more beneficial than DLPFC (7,8).…”
Section: Introductionmentioning
confidence: 66%